Supply Chain Management: Moderating Affect of COVID-19 on the Relationship of Logistics Performance and Supply Chain Resilience - Saeed, Iqra; Arshad, Kamran (Journal of Applied Research and Multidisciplinary Studies, 2021)
The aim of the study is to examine the correlation between Logistic performance and Supply Chain resilience and with COVID-19 as moderator. Quantitative research was conducted for this study which questionnaire was adapted from (World Bank LPI_2018_Questionaitre) 12 number of respondents were responded on the closed ended questionnaire. The theory of constraint, the strength of the supply chain link that can dictate the effectiveness and efficiency of the supply chain partnership and the ultimate success of the supply chain. According to the results, positive relationship exists between the Logistics performance and Supply Chain Resilience. A very weakening effect was observed on COVID-19 pandemic as moderator. The results of hypothesis indicated that H1 Logistics performance index plays a substantial role in enhancing the supply chain resilience and H2 Covid-19 significantly moderates relationship of logistics performance index and supply chain resilience.